2015
DOI: 10.1074/jbc.m114.619890
|View full text |Cite
|
Sign up to set email alerts
|

p53 Degradation by a Coronavirus Papain-like Protease Suppresses Type I Interferon Signaling

Abstract: Background: The molecular mechanism of coronavirus PLPs suppressing the innate immune response remains unclear. Results: PLP2 induces the degradation of p53 through stabilizing MDM2, and IRF7 is a novel target gene of p53. Conclusion: PLP2 inhibits the p53-mediated production of type I IFN and apoptosis to ensure viral growth. Significance: We identify the mechanism with which coronavirus induces the low dosage IFN production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
115
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(119 citation statements)
references
References 33 publications
0
115
1
Order By: Relevance
“…In 2015, Yuan et al . found that p53 can upregulate the transcription of IRF7. HCoV‐NL63 PL2 pro deubiquitinates and stabilizes MDM2, a p53 degradation stimulator, thus causing p53 degradation and blocking the p53–IRF7–IFNβ signaling pathway (Fig.…”
Section: Rna‐virus Proteases Interfering With the Host Innate Immunementioning
confidence: 95%
See 1 more Smart Citation
“…In 2015, Yuan et al . found that p53 can upregulate the transcription of IRF7. HCoV‐NL63 PL2 pro deubiquitinates and stabilizes MDM2, a p53 degradation stimulator, thus causing p53 degradation and blocking the p53–IRF7–IFNβ signaling pathway (Fig.…”
Section: Rna‐virus Proteases Interfering With the Host Innate Immunementioning
confidence: 95%
“…HCoV‐NL63 PL2 pro deubiquitinates and stabilizes MDM2, a p53 degradation stimulator, thus causing p53 degradation and blocking the p53–IRF7–IFNβ signaling pathway (Fig. A) . p53 also inhibits SARS‐CoV replication .…”
Section: Rna‐virus Proteases Interfering With the Host Innate Immunementioning
confidence: 99%
“…In addition, the HCoV-NL63 PL2 pro was shown to block the p53-IRF7-IFNβ signaling pathway (Yuan et al, 2015). p53 can induce type-I interferon production via IRF7 (interferon regulatory factor 7; Yuan et al, 2015).…”
Section: Papain-like Protease 2 (Pl2 Pro )mentioning
confidence: 99%
“…On the other hand, many viruses have also developed strategies to manipulate host p53 signalling pathways to increase virus replication (Casavant et al, ; Royds et al, ). For example, coronavirus inhibited p53‐mediated host apoptosis to ensure viral growth in infected cells (Yuan et al, ). In our study, RGNNV infection reduced the expression of Ljp53 at 48 hpi, which at least partially inhibited the host cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%